2022
DOI: 10.3390/ijerph191811587
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and Preliminary Validation of the Fear of Coronavirus Vaccination Scale in the Prospective Study among a Representative Sample of Polish, Israeli, Slovenian, and German Adults during the COVID-19 Pandemic

Abstract: Although concerns about harm and side effects are among the most important factors determining vaccine hesitancy, research on the fear of vaccination is sparse. The purpose of this study is a validation the Fear of Coronavirus Vaccination Scale (FoCVVS), adapted from the Fear of COVID-19 Scale. A representative sample of 1723 young adults aged 20–40 from Poland, Israel, Slovenia, and Germany participated during two time-points of the third COVID-19 pandemic wave. The online survey included demographic variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 57 publications
3
7
0
Order By: Relevance
“…It is in line with the results obtained by Huang et al, who observed that at 6 months after the COVID-19 pandemic began, patients were at greater risk of sleep difficulties, and anxiety or depression [69]. In the literature it is also reported that mental health problems might be one of the reasons for patient's lack of vaccine acceptance [70]. However, it is associated mainly with lack of trust in science, governments, and so-called 'conspiratorial thinking' about COVID-19 [71].…”
Section: Status Of Vaccination Against Covid-19 and Confirmed Infecti...supporting
confidence: 89%
“…It is in line with the results obtained by Huang et al, who observed that at 6 months after the COVID-19 pandemic began, patients were at greater risk of sleep difficulties, and anxiety or depression [69]. In the literature it is also reported that mental health problems might be one of the reasons for patient's lack of vaccine acceptance [70]. However, it is associated mainly with lack of trust in science, governments, and so-called 'conspiratorial thinking' about COVID-19 [71].…”
Section: Status Of Vaccination Against Covid-19 and Confirmed Infecti...supporting
confidence: 89%
“…The 30 items were newly developed and relevant literature that we consulted to inform item development and topics that should be measured by the questionnaire items were the Vaccine Hesitancy Survey Questions from the WHO (World Health Organization, 2018), the Fear of COVID-19 Scale (Ahorsu et al, 2020), the Motors of COVID-19 Vaccination Acceptance Scale (Chen et al, 2021), and the COVID-19 Student Stress Questionnaire (Ochnik, Rogowska, Benatov, & Arzenšek, 2022;Zurlo, Cattaneo Della Volta, & Vallone, 2020). The 30 items were then presented to members of a professional panel consisting of psychologists, epidemiologists, biostatisticians, dentists, and public health and Indigenous health experts, which comprised the research team behind the CIS development.…”
Section: Development Of the Covid-19 Impact Scalementioning
confidence: 99%
“…Research on this topic often provides the relevant information needed for the development of interventions that are aimed at reducing fear, particularly given that fear symptoms are relatively identifiable and manageable [15]. However, it is noteworthy that there is a notable lack of reliable tools available for measuring the impact of fear, which might explain the scarcity of studies in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Ochnik et al [15] developed and validated the Coronavirus Vaccination Fear Scale (FoCVVS) concerning the German, Polish, Slovenian, and Hebrew languages, following the same methodology used by Malas and Tolsá [9] in creating the VFS-6. Despite both scales starting from the same methodology, there are certain differences between them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation